Medication safety in an acute teaching hospital: an Irish perspective (Italian Journal of Public Health, 2005)
Background In line with international trends, patient safety has become a priority health issue in the Irish healthcare system in recent years. In August 2004, a medication safety facilitator (MSF) was appointed in an acute teaching hospital in Ireland for the investigation of medication safety events (MSEs).Methods The MSF designed a pilot medication safety reporting system for trial in three ward areas over seven months. The system was subsequently expanded to the entire hospital.Results During the first year of the appointment of the MSF, reporting levels increased by 290% relative to the same period the previous year. The majority of reports involved potential risks, near misses and medication errors that reached the patient but caused no discernable harm. For the more serious events, a root cause analysis was undertaken and action plans were developed by collaboration between the MSF and ward staff. A system of regular feedback to staff was introduced to encourage continued reporting and heightened awareness of medication safety issues. Proactive safety reviews were undertaken for high-risk medications, resulting in the introduction of system changes to optimise safety. Guidance was provided to staff in the form of bulletins, alerts and education sessions.Future plans Expansion plans for the second year of the project involve the development of a network of safety champions across the hospital. These individuals will undergo root cause analysis training and then liaise with the MSF with regard to the communication of safety messages and the implementation of action plans.
Keywords: Medication; safety; Ireland